THE INFLUENCE OF WORK ENVIRONMENT AND MOTIVATION ON EMPLOYEE PRODUCTIVITY AT DPRD SUMATRA UTARA - Sinta Romarito Tampubolon; Muhammad Yalzamul Insan; Ara Auza (FISIP Universitas Malikussaleh, 2026)
Indonesia is entering a demographic bonus period that will peak in 2030, thus opening up great opportunities for national economic growth. Increasing the proportion of the productive age population can boost productivity and GDP growth if supported by adequate quality of human resources. However, challenges arise in the bureaucratic sector, including in the Secretariat of the North Sumatra Provincial DPRD, which faces a high workload and a less conducive work environment. Therefore, this study aims to analyze the influence of work environment and work motivation on employee productivity to support the improvement of performance and quality of public services. The approach used was quantitative with a survey method, through the distribution of questionnaires to 71 respondents. The data obtained were analyzed using multiple linear regression with the help of SPSS version 26. The results showed that partially, the work environment did not have a significant effect on work productivity (significance value 0.457 > 0.05), while work motivation had a partial significant effect on employee work productivity (significance value 0.022 < 0.05). Simultaneously, the two independent variables had a significant effect on employee work productivity with a significance value of 0.031 and a determination coefficient (R²) of 0.096. This shows that 9.6% of the variation in work productivity can be explained by these two variables.